“Everything Changes”: Listening to Homicidally Bereaved Individuals’ Practice and Intervention Needs - Alves-Costa, Filipa (Journal of interpersonal violence, 2021)
This study sought to understand how individuals bereaved through homicide (murder or manslaughter) describe their postevent experiences to inform clinical needs and promote mechanisms for change. A total of 21 participants (18 females) between the ages of 29 and 66 (M age = 47.81 years, SD = 8.99) took part in this study. They were all participating in a residential program for homicidally bereaved individuals and were all residents in the United Kingdom. The sample comprised of 12 parents, five siblings, one partner, one daughter, one friend, and one grandmother of the deceased. The length of time since the bereavement varied from 12 months to 18 years (M = 2.48, SD = 1.80). Thematic analysis was used to analyze the narratives collected. Three central themes emerged, namely (a) uniqueness of the experience, (b) changed self and world, and (c) mixed experiences of support. The uniqueness of the individuals’ experiences was associated with the nature of the homicide event and the consequences that are unlikely to occur in “normal” deaths (e.g., judiciary). A sense of a changed self (e.g., ongoing emotional/mental and physical responses, coping) and world (e.g., changed beliefs regarding safety and criminal activity) seemed to be contributing to different shades of (mal)adjustment. Adaptive and protective strategies were identified. The current study with a large qualitative sample generated a unique, rich description/integration about individuals’ journeys following an experience of homicidal bereavement. Findings are likely to inform policy and clinical practice by considering individuals’ voices.